A Systematic Literature Review on ICT Integration: Opportunities and Challenges in Teaching Mathematics - Enorme, Czarina; Santidad, Judy; Ledesma, Chrizl; Dioneda, Mary; Borja, Joanna (International Journal on Integrated Education, 2024)
Integrating information and communication technology in modern education is very instrumental in changing the way mathematics is taught and learned. Research in the Philippines explores how ICT is integrated into the country's teaching of math, outlining opportunities and challenges for Filipino teachers and students. This study used a systematic literature review with the aid of the PRISMA framework. A total of 22,800 scholarly articles in Google Scholar was reduced to 994 after title and keyword screening. After the final analysis, 12 articles met all criteria. Literature review shows that integrating ICT into math education offers an incredible number of benefits such as increased student engagement, new pedagogies, improved classroom management, flexibility in learning and teaching, and enhanced assessment. ICT improves contact between teachers and students as it creates possibilities for computer-supported collaborative learning using tools such as virtual manipulatives and simulations to deepen understanding of skills referred to as higher-order thinking. Several challenges still exist despite the benefits. Most schools lack proper ICT infrastructure: reliable internet and enough devices. The budget makes it hard to acquire equipment or relevant software needed for such instruction. Some teachers are not confident and need training in using ICT, and technical support is not adequate. These will only lead to uneven use of ICT in classrooms, hence limiting the possible impact on mathematics teaching. Infrastructural improvements, funds, and training of teachers, when coupled with technical support, might propel more efficient integration of ICT in math instructions within Philippine education. These will build vibrant learning environments that pave the way for learners toward success in a world increasingly dominated by digital technology.